Parents' opinions of kindergarten education and their relationships to certain variables - Cabag, Susana V. 1921- (s.n.], 1967)
This study presents the parents' thoughts on the following: functions of kindergarten education, qualities of a good kindergarten school, activities that should be included in a kindergarten curriculum, the important traits of a kindergarten teacher, and the duties of a kindergarten teacher. The relationships of these opinions to certain variables are also determined.